2018
DOI: 10.1186/s41043-018-0144-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a typhoid fever epidemic in Moyale Sub-County, Kenya, 2014–2015

Abstract: AimTyphoid fever is a vaccine-preventable bacterial disease that causes significant morbidity and mortality throughout Africa. This paper describes an upsurge of typhoid fever cases in Moyale Sub-County (MSC), Kenya, 2014–2015.MethodsWe conducted active hospital and health facility surveillance and laboratory and antimicrobial sensitivity testing for all patients presenting with headache, fever, stomach pains, diarrhea, or constipation at five MSC health facilities between December 2014 and January 2015. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 9 publications
3
23
1
Order By: Relevance
“…The association of Salmonella infection with eating in restaurant is an indication some restaurants do not observe proper hygienic conditions for food preparation and storage, hence increasing the likelihood of Salmonella infection. [3,6] The study found all Salmonella isolates sensitive to ceftriaxone and ciprofloxacin comparable to a study conducted in Kenya. [17] It should be noted that resistance of Salmonella spp to fluoroquinolones has been reported in Uganda and Japan.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…The association of Salmonella infection with eating in restaurant is an indication some restaurants do not observe proper hygienic conditions for food preparation and storage, hence increasing the likelihood of Salmonella infection. [3,6] The study found all Salmonella isolates sensitive to ceftriaxone and ciprofloxacin comparable to a study conducted in Kenya. [17] It should be noted that resistance of Salmonella spp to fluoroquinolones has been reported in Uganda and Japan.…”
Section: Discussionsupporting
confidence: 51%
“…[4,5,9] On the other hand, our finding was lower than the study conducted in Kenya. [6] The variation between studies on Salmonella infection could be due to differences in the type of patients enrolled such as age, immune status or underlying conditions, predisposing factors, as well as variations in bacteriological techniques and specimen used. In some studies, like the present one, only stool culture was performed, while other studies performed blood and stool cultures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations